Impact of growth hormone on IVF/ICSI outcomes and endometrial receptivity of patients undergoing GnRH antagonist protocol with fresh embryo transfer: a pilot study - Chu, Yifan; Wang, Luyao; Xie, Jiaxin; Yang, Shulin; Liu, Si; Hu, Dan; Yue, Jing (Frontiers in Endocrinology, 2023)
Introduction: Gonadotropin-releasing hormone antagonist (GnRH-ant) protocol is widely used in the world for controlled ovarian hyperstimulation (COH). However, previous studies have shown that pregnancy outcomes of fresh embryo transfer with GnRH-ant protocol are not ideal. Current studies have demonstrated the value of growth hormone (GH) in improving the pregnancy outcome of elderly women and patients with diminished ovarian reserve, but no prospective studies have confirmed the efficacy of GH in fresh embryo transfer with GnRH-ant protocol, and its potential mechanism is still unclear. This study intends to evaluate the impact of GH on IVF/ICSI outcomes and endometrial receptivity of patients undergoing GnRH-ant protocol with fresh embryo transfer, and preliminarily explore the possible mechanism. Methods: We designed a randomized controlled trial of 120 infertile patients with normal ovarian response (NOR) who will undergo IVF/ICSI from April 2023 to April 2025, at Department of Reproductive Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology. The patients will be divided into the depot gonadotropin-releasing hormone agonist (GnRH-a) protocol group, GnRH-ant protocol control group, and GnRH-ant protocol plus GH intervention group at a ratio of 1:1:1 by block randomization design. Patients will be followed on enrollment day, trigger day, embryo transfer day, 7 days after oocytes pick-up, 15 days after embryo transfer, 28 days after embryo transfer, and 12 weeks of gestation. The primary outcome is the ongoing pregnancy rate. Secondary outcomes include the gonadotropin dosage, duration of COH, endometrial thickness and pattern, luteinizing hormone, estradiol, progesterone level on trigger day, numbers of retrieved oocytes, high-quality embryo rate, biochemical pregnancy rate, clinical pregnancy rate, implantation rate, ectopic pregnancy rate, early miscarriage rate, multiple pregnancy rate and incidence of moderate and severe ovarian hyperstimulation syndrome. The endometrium of certain patients will be collected and tested for endometrial receptivity. Ethics and Dissemination: The study was approved by the Ethics Committee of Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology [approval number: TJ-IRB20230236; approval date: February 10, 2023]. The research results will be presented at scientific/medical conferences and published in academic journals. Trial Registration: Chinese Clinical Trial Registry; identifier: ChiCTR2300069397